Factors Affecting Utilization of Modern Family Planning Method among Women with Psychiatric Illness Attending Psychiatric Outpatient Services at Amanuel Mental Specialized Hospital Addis Ababa, Ethiopia, 2018. An Institution Based Cross-Sectional Study - Seid, Abdu; Wordofa, Berhanu; Tesfaye, Jembere (Ethiopian Journal of Reproductive Health, 2021)
ABSTRACT Background: Barriers to effective use of contraception on the part of mentally ill patients magnified by their inability to establish reliable, long-term approaches to pregnancy prevention. The prevalence of unplanned pregnancies are high among psychiatric patients, due to the frequent lack of insight, lack of planning and behavioral control and potential medication interaction between hormonal contraceptives and some psychotropic drugs reducing contraceptive effectiveness. Therefore, Women who are mentally ill or who abuse drugs should be considered for the full range of contraceptive options. Objective: To assess utilization and associated factors of modern family planning method among women with psychiatric illness attending psychiatric outpatient services at Amanuel mental specialized hospital Addis Ababa, Ethiopia 2018. Method: Institution based cross-sectional study design was conducted to assess utilization and associated factors of modern family planning method among women with psychiatric illness attending psychiatric outpatient services and 413 study subjects were selected using systematic random sampling technique. Bivariate and multivariate analysis was carried out to determine the association between an independent variable with the outcome variable among study participants during the period of the study at Amanuel mental specialized hospital in Addis Ababa, Ethiopia. Result: out of the total sampled women with psychiatric illness (40.2%) of the respondents were using modern family planning methods at the time of the study. According to the multiple logistic regressions at 95% C.I, educational level, resident, employment and counseling about family planning by staff found to be independently associated with utilization of modern family planning method. Conclusion: In this study, 40.3% of them currently use a modern family planning method. Male condoms and injectable were the most known type of method. Moreover, injectable was the most common currently used method. Healthcare provider should be strengthening family planning counseling to enhance knowledge and utilization of modern family planning at mental health clinic and community level. Key words: utilization, modern family planning, associated factors, mental illness, Addis Ababa